Silver phosphanes partnered with carborane monoanions: synthesis, structures and use as highly active Lewis acid catalysts in a hetero-Diels-Alder reaction. - Patmore, N; Hague, C; Cotgreave, J; Mahon, M; Frost, C; Weller, A (2002)
Four Lewis acidic silver phosphane complexes partnered with [1-closo-CB(11)H(12)](-) and [1-closo-CB(11)H(6)Br(6)](-) have been synthesised and studied by solution NMR and solid-state X-ray diffraction techniques. In the complex [Ag(PPh(3))(CB(11)H(12))] (1), the silver is coordinated with the carborane by two stronger 3c-2e B-H-Ag bonds, one weaker B-H-Ag interaction and a very weak Ag.C(arene) contact in the solid state. In solution, the carborane remains closely connected with the [Ag(PPh(3))](+) fragment, as evidenced by (11)B chemical shifts. Complex 2 [Ag(PPh(3))(2)(CB(11)H(12))](2) adopts a dimeric motif in the solid state, each carborane bridging two Ag centres. In solution at low temperature, two distinct complexes are observed that are suggested to be monomeric [Ag(PPh(3))(2)][CB(11)H(12)] and dimeric [Ag(PPh(3))(2)(CB(11)H(12))](2). With the more weakly coordinating anion [CB(11)H(6)Br(6)](-) and one phosphane, complex 3 [Ag(PPh(3))(CB(11)H(6)Br(6))] is isolated. Complex 4, [Ag(PPh(3))(2)(CB(11)H(6)Br(6))], has been characterised spectroscopically. All of the complexes have been assessed as Lewis acids in the hetero-Diels-Alder reaction of N-benzylideneaniline with Danishefsky's diene. Exceptionally low catalyst loadings for this Lewis acid catalysed reaction are required (0.1 mol %) coupled with turnover frequencies of 4000 h(-1) (quantitative conversion to product after 15 minutes using 3 at room temperature). Moreover, the reaction does not occur in rigorously dry solvent as addition of a substoichiometric amount of water (50 mol %) is necessary for turnover of the catalyst. It is suggested that a Lewis assisted Brønsted acid is formed between the water and the silver. The effect of changing the counterion to [BF(4)](-), [OTf](-) and [ClO(4)](-) has also been studied. Significant decreases in reaction rate and final product yield are observed on changing the anion from [CB(11)H(6)Br(6)](-), thus demonstrating the utility of weakly coordinating carborane anions in organic synthesis.